Effects of PEERS® Social Skills Training on Young Adults with Intellectual and Developmental Disabilities During College. Issue 2 (March 2021) - Rose, Amy J.; Kelley, Kelly R.; Raxter, Alexandra
The Program for the Education and Enrichment of Relational Skills (PEERS ® ) was used to provide weekly social skills training to a group of 10 college students with intellectual and developmental disabilities (IDD) between ages 18 and 26 attending an inclusive residential postsecondary college program. Additionally, Circles curriculum was used to supplement the PEERS curriculum for teaching social relationship boundaries. An average of 12 sessions per semester of PEERS ® training sessions were conducted over each academic year. The present study examines the impact of the program on social skills, friendship qualities, and conversational skills. Results showed increased social skill knowledge, friendship quality, and conversational skills from pretest to posttest intervention. In this paper, we discuss the training program, results, implications for practice, limitations, and future research needs.